A Bayesian examination of the relationship of internal and external touchpoints in the customer experience process across various service environments. (March 2020) - Siqueira, Jose Ribamar; ter Horst, Enrique; Molina, German; Losada, Mauricio; Mateus, Marelby Amado
Abstract: Customer experience (CX) is an aggregate of consumer touch points that can be brand-owned (completely controlled by the firm), partner-owned (collectively controlled by the firm and one or more of its partners), customer-owned (where the firm or its partner cannot exert any control or influence) or represented by social/external touch points that account for the importance of the roles of others in the customer experience process. Although the concept of CX is widely used, not much has been examined about how external touch points impact customer perception of experience. Therefore, the main purpose of this study is to examine the role and impact of internal and external touchpoints as dimensions of customer experience and how CX can impact consumer word-of-mouth intention. Service outcome and peace of mind were used to represent internal experience touchpoints and peer to peer quality (PTP) was used to represent an external experience touchpoint. A total of 293 usable surveys were used for analysis using a Bayesian model developed for this study instead of the more traditional SEM approaches. Results showed that an external experience touchpoint has a similar impact to those of internal experience touchpoints in the experience process. CX was also found to have a strong effect on customer word of mouth intention. These findings make various contributions to the literature on CX, especially to research differentiating internal from external experience touchpoints. On the practical side, this study provides recommendations to retailers about how to manage an external touchpoint.